A 2‐in‐1 single‐element coil design for transcranial magnetic stimulation and magnetic resonance imaging. Issue 1 (10th February 2017) - Lu, Hai; Wang, Shumin
Abstract : Purpose: To demonstrate the feasibility of turning transcranial magnetic stimulation (TMS) coil for MRI signal reception. Methods: A critically coupled network was formed by using a resonated turn of TMS coil as the secondary and a regular radiofrequency (RF) coil as the primary. A third coil was positioned between the two coils for detuning during RF transmission. Bench measurement, numerical simulation, and MRI experiment were performed for validation. Results: The signal‐to‐noise ratio of the proposed 2‐in‐1 coil is 35% higher in its field of view, compared with a MRI‐only reference coil of the same size, made by the same material, and backed up by an untuned TMS coil, but lower than a RF surface coil of the same size without any TMS coil nearby. Spin‐echo images of the human brain further validated its performance. Conclusions: The proposed method can transform TMS coil for MRI signal acquisition with virtually no modifications on the TMS side. It not only enables flexible and close positioning of TMS coil inside MRI scanner, but also improves the signal‐to‐noise ratio compared with conventional implementations. It can be applied as a building block for developing advanced concurrent TMS/MRI hardware. Magn Reson Med 79:582–587, 2018. © 2017 International Society for Magnetic Resonance in Medicine.